DEATH CRIME AGAINST SEXUAL VIOLENCE (RAPE OF 12 STUDENTS IN BANDUNG) IN A RESTORATIVE JUSTICE PERSPECTIVE - Murshal Senjaya (International Journal of Social Science, 2021)
Herry (Santriwati Rape Case in Bandung) is suspected of having violated a criminal offense Article 81 paragraph (1), paragraph (3) in conjunction with Article 76.D of the Republic of Indonesia Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection in conjunction with Article 65 paragraph (1) of the Criminal Code. The settlement of criminal cases can still be carried out amicably or based on restorative justice based on the following provisions:Prosecutor's Office Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice (“Agency 15/2020”). Regulation of the Head of the National Police of the Republic of Indonesia Number 6 of 2019 concerning Criminal Investigation (“Perkapolri 6/2019”).Circular Letter of the Head of the State Police of the Republic of Indonesia Number SE/8/VII/2018 Year 2018 concerning the Application of Restorative Justice (Restorative Justice) in the Settlement of Criminal Cases (“SE Kapolri 8/2018”).